Older Adults Accessing HIV Care and Treatment and Adherence in the IeDEA Central Africa Cohort - Jamie Newman; Jeniffer Iriondo-Perez; Jennifer Hemingway-Foday; Anna Freeman; Wilfred Akam; Ashu Balimba; Lucien Kalenga; Marcel Mbaya; Brigitte Mfangam Molu; Henri Mukumbi; Théodore Niyongabo; Joseph Atibu; et al. (AIDS Research and Treatment)
Background. Very little is known about older adults accessing HIV care in sub-Saharan Africa. Materials and Methods. Data were obtained from 18,839 HIV-positive adults at 10 treatment programs in Burundi, Cameroon, and the Democratic Republic of Congo. We compared characteristics of those aged 50+ with those aged 18–49 using chi-square tests. Logistic regression was used to determine if age was associated with medication adherence. Results. 15% of adults were 50+ years. Those aged 50+ were more evenly distributed between women and men (56% versus 44%) as compared to those aged 18–49 (71% versus 29%) and were more likely to be hypertensive (8% versus 3%) (P<0.05). Those aged 50+ were more likely to be adherent to their medications than those aged 18–49 (P<0.001). Adults who were not heavy drinkers reported better adherence as compared to those who reported drinking three or more alcoholic beverages per day (P<0.001). Conclusions. Older adults differed from their younger counterparts in terms of medication adherence, sociodemographic, behavioral, and clinical characteristics.